A germline-specific role for the mTORC2 component Rictor in maintaining spermatogonial differentiation and intercellular adhesion in mouse testis. (9th February 2018) - Bai, Shun; Cheng, Le; Zhang, Yingwen; Zhu, Chunsen; Zhu, Zhiping; Zhu, Ruping; Cheng, C Yan; Ye, Lan; Zheng, Ke
Abstract: STUDY QUESTION: What is the physiological role of Rictor in spermatogenic cells? SUMMARY ANSWER: Germline expression of Rictor regulates spermatogonial differentiation and has an essential role in coordinating germ cells and Sertoli cells in maintaining intact cell–cell adhesion dynamics and cytoskeleton-based architecture in the seminiferous epithelium. WHAT IS KNOWN ALREADY: The mechanistic target of rapamycin (mTOR) resides in its functions as the catalytic subunits of the structurally and functionally distinct mTORC1 and mTORC2 complexes. In the mammalian testis, mTORC1 regulates spermatogonial stem cell self-renewal and differentiation, whereas mTORC2 is required for Sertoli cell function. In contrast to mTORC1, mTORC2 has been much less well studied. Rictor is a distinct component of the mTORC2 complex. STUDY DESIGN, SIZE, DURATION: We investigated the effects of germ cell-specific ablation of Rictor on testicular development by using a mouse model of germline-specific ablation of Rictor . PARTICIPANTS/MATERIALS, SETTING, METHODS: We analyzed the in-vivo functions of Rictor through different methods including histology, immunofluorescent staining, chromosome spreads, blood–testis barrier (BTB) integrity assays and RNA sequencing. MAIN RESULTS AND THE ROLE OF CHANCE: Mutant mice did not show a defect in meiotic synapsis or recombination, but exhibited compromised spermatogonial differentiation potential, disorganized cell–cell junctions, impaired BTB dynamics and defective spermiogenesis. Concomitantly, RNA-seq profiling revealed that many genes involved in adhesion and migration were expressed inappropriately. LARGE SCALE DATA: RNA-seq data are published in the SRA database (PRJNA419273). LIMITATIONS REASONS FOR CAUTION: A detailed analysis of the mechanisms underlying the phenotype needs further investigations. WIDER IMPLICATIONS OF THE FINDINGS: Our work provides previously unidentified in-vivo evidence that germline expression of Rictor plays a role in maintaining spermatogonial differentiation and cell–cell adhesion. These findings are important for understanding the regulation of spermatogenesis and have clinical implications for the effect of mTOR inhibitors on human fertility. STUDY FUNDING AND COMPETING INTEREST(S): This study was supported by National Key R&D Program of China (2016YFA0500902), National Natural Science Foundation of China (31471228 and 31771653), Jiangsu Science Foundation for Distinguished Young Scholars (BK20150047), and Natural Science Foundation of Jiangsu Province (BK20140897, 14KJA180005 and 14KJB310004) to K.Z. The authors declare no competing or financial interests.